2016
DOI: 10.1021/acs.jpca.6b05898
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Hydrogen Bonding in Substituted Aminoalcohols

Abstract: The qualifying features of a hydrogen bond can be contentious, particularly where the hydrogen bond is due to a constrained intramolecular interaction. Indeed there is disagreement within the literature whether it is even possible for an intramolecular hydrogen bond to form between functional groups on adjacent carbon atoms. This work considers the nature of the intramolecular interaction between the OH (donor) and NH2 (acceptor) groups of 2-aminoethanol, with varying substitution at the OH carbon. Gas-phase v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…Unequivocally, the bcp is the point where one finds no difference between QTAIM and RDG. elucidated in several recent studies by the Kjaergaard group [67][68][69][70][71], in which it was shown that the experimentally-determined weakly bound and van der Waals interactions in molecular systems can be successfully identified and characterized by RDG-NCI, which may or may not be identified with QTAIM due to its stringent criteria.…”
Section: A Reduced Density Gradient (Rdg) Description Of Non-covalentmentioning
confidence: 99%
“…Unequivocally, the bcp is the point where one finds no difference between QTAIM and RDG. elucidated in several recent studies by the Kjaergaard group [67][68][69][70][71], in which it was shown that the experimentally-determined weakly bound and van der Waals interactions in molecular systems can be successfully identified and characterized by RDG-NCI, which may or may not be identified with QTAIM due to its stringent criteria.…”
Section: A Reduced Density Gradient (Rdg) Description Of Non-covalentmentioning
confidence: 99%
“…29 NCI theory is a complementary approach to the more traditional Atoms in Molecules (AIM) topological analysis of electron density, 30 and offers some advantages particularly for weak intramolecular hydrogen bonding interactions. 31,32 To date, NCI theory has largely been used for a qualitative interpretation of hydrogen bond strength although Contreras-Garcia et al…”
mentioning
confidence: 99%
“…4 This investigation expands on recent work by some of the authors, who showed that the OH-stretching frequency of substituted amino alcohols that exhibit an intramolecular OH-N hydrogen bond correlates well with the kinetic energy integrated within an NCI isosurface volume. 32 Spectra of the gas phase complexes were obtained by subtracting the individual monomer spectra from the spectrum of the mixture (e.g. MeOH + pyridine).…”
mentioning
confidence: 99%
“…14 The major gt conformation of 2 and 3 in aqueous base is also consistent with the predominant gauche conformation of neutral ethanol amine as determined by NMR spectroscopy, 14 and computationally, 15 and as determined by vibrational spectroscopy in the gas phase. 16 …”
Section: Resultsmentioning
confidence: 99%